Mechanical properties of epithelial cells in domes investigated using atomic force microscopy - Shigemura, Kenta; Kuribayashi-Shigetomi, Kaori; Tanaka, Ryosuke; Yamasaki, Haruka; Okajima, Takaharu (Frontiers in Cell and Developmental Biology, 2023)
As epithelial cells in vitro reach a highly confluent state, the cells often form a microscale dome-like architecture that encloses a fluid-filled lumen. The domes are stabilized by mechanical stress and luminal pressure. However, the mechanical properties of cells that form epithelial domes remain poorly characterized at the single-cell level. In this study, we used atomic force microscopy (AFM) to measure the mechanical properties of cells forming epithelial domes. AFM showed that the apparent Young's modulus of cells in domes was significantly higher when compared with that in the surrounding monolayer. AFM also showed that the stiffness and tension of cells in domes were positively correlated with the apical cell area, depending on the degree of cell stretching. This correlation disappeared when actin filaments were depolymerized or when the ATPase activity of myosin II was inhibited, which often led to a large fluctuation in dome formation. The results indicated that heterogeneous actomyosin structures organized by stretching single cells played a crucial role in stabilizing dome formation. Our findings provide new insights into the mechanical properties of three-dimensional deformable tissue explored using AFM at the single-cell level.